Persepsi Masyarakat Tentang Program KKN dan Dampaknya terhadap Sosial Budaya Desa Kebonagung - Naufal Nur Sahid; Nurul Hikmah; Mughofur Dela Prayoga; Alvian Hidayat; M. Rouful Husna; Putri Siti Chairiyah; Irman Said Prastyo (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to reveal the perception of the people of Kebonagung Village towards the Real Work Lecture (KKN) program and its impact on the socio-cultural aspects of Kebonagung Village. This study uses a qualitative method with a case study approach. The results of the study show that public perception of KKN varies, ranging from positive to skeptical. Factors that affect this perception include direct experience with the KKN program, the level of education, and the level of involvement in village activities. In addition, this study also found that KKN has a positive impact on the socio-cultural aspects of the village, such as increasing public awareness, changing behavior, and strengthening mutual cooperation values.